Pliocene oceanic seaways and global climate - Karas, Cyrus; Bahr, André (Scientific reports, 2017)
Tectonically induced changes in oceanic seaways had profound effects on global and regional climate during the Late Neogene. The constriction of the Central American Seaway reached a critical threshold during the early Pliocene ~4.8-4 million years (Ma) ago. Model simulations indicate the strengthening of the Atlantic Meridional Overturning Circulation (AMOC) with a signature warming response in the Northern Hemisphere and cooling in the Southern Hemisphere. Subsequently, between ~4-3 Ma, the constriction of the Indonesian Seaway impacted regional climate and might have accelerated the Northern Hemisphere Glaciation. We here present Pliocene Atlantic interhemispheric sea surface temperature and salinity gradients (deduced from foraminiferal Mg/Ca and stable oxygen isotopes, δ18O) in combination with a recently published benthic stable carbon isotope (δ13C) record from the southernmost extent of North Atlantic Deep Water to reconstruct gateway-related changes in the AMOC mode. After an early reduction of the AMOC at ~5.3 Ma, we show in agreement with model simulations of the impacts of Central American Seaway closure a strengthened AMOC with a global climate signature. During ~3.8-3 Ma, we suggest a weakening of the AMOC in line with the global cooling trend, with possible contributions from the constriction of the Indonesian Seaway.
Published: 05 January 2017
Gesehen am 26.06.2018